Aged metastable high-entropy alloys with heterogeneous lamella structure for superior strength-ductility synergy. (15th October 2020) - Zhang, Cheng; Zhu, Chaoyi; Cao, Penghui; Wang, Xin; Ye, Fan; Kaufmann, Kevin; Casalena, Lee; MacDonald, Benjamin E.; Pan, Xiaoqing; Vecchio, Kenneth; Lavernia, Enrique J.
Abstract: High-entropy alloys containing multi-principal-element systems significantly expand the potential alloy design space, and offer the possibility of overcoming the strength-ductility trade-off in metallurgical research. However, the gain in ultra-high strength through traditional grain refinement and precipitation-strengthening mechanisms inevitably leads to a drastic loss of ductility. Here, we report on the design and fabrication of heterogeneous-lamella structured, aged bulk high-entropy alloy, which attains gigapascal tensile strength while retaining excellent ductility (UTS ~1.4 GPa, elongation ~30%; UTS ~1.7 GPa, elongation ~10%). Our work shows that the improved strength-ductility synergy arises due to various complementary strengthening mechanisms, including solid-solution, interfaces, precipitation and martensitic transformation, which influence the hardening and deformation processes at different strain levels. In particular, the hetero-deformation that is associated with the formation of microbands as well as the stress-induced martensite promotes additional hardening and hence high ductility. The strategy described here, that is leveraging the concept of heterogeneous microstructure design, provides a practical and novel method for fabricating high-performance structural materials. Graphical abstract: Summary of various strengthening and deformation mechanisms in aged HL-NCATB HEAs. Image, graphical abstract